Find the force of interaction-3

Consider two non conducting solid cylinders each having length L and radius R, such that R<<L. Both of them have charge density ρ \rho . They are placed such that the distance between their axes(parallel to each other) is R. Find the force of interaction between the cylinders in Newtons . The cross-section of the arrangement is shown below:

Details and assumptions:

  • ρ = 100 μ C / m 3 \rho = 100 \mu C/m^3

  • R = 0.1 m R = 0.1 m

  • L = 10 m L = 10 m

Note: I am really sorry for those who have tried it before the answer correction. Actually, there was an error in my input to calculator . Also, the answer is not 2 ρ 2 R 3 L 9 ϵ 0 ( 8 π ) \dfrac{2\rho^2 R^3 L}{9 \epsilon_{0}} (8 - \pi) , as was in the dispute sent by someone.


The answer is 10.41.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Jatin Yadav
Oct 7, 2014

Clearly, as R < < L R<<L , the electric field(radial from axis) due to the cylinder is given by :

E ( r ) = { ρ r 2 ϵ 0 , if r R ρ R 2 2 r ϵ 0 , if r > R , r < < L E(r) = \begin{cases} \dfrac{\rho r}{2 \epsilon{0}} , & \text{if }r \leq R \\ \dfrac{\rho R^2}{2 r \epsilon_{0}}, & \text{if } r>R , r<< L \end{cases}

Now, consider an arc of thickness of radius r r , and d r dr one one of the cylinder, whose center coincides with the center of other cylinder as shown :

Now , clearly, the horizontal force on a small element on the arc corresponding to angle θ \theta , where θ \theta varies from ϕ - \phi to ϕ \phi is E ( r ) ρ r L cos θ d θ d r E(r) \rho r L \cos \theta d \theta dr

Hence , the net force of interaction is given by:

F = 0 2 R ρ L r E ( r ) ( ϕ ϕ cos θ d θ ) d r F = \displaystyle \int_{0}^{2R} \rho L r E(r) \bigg(\int_{- \phi}^{\phi}\cos \theta d \theta\bigg) dr

= 0 2 R 2 ρ L r E ( r ) sin ϕ d r \displaystyle \int_{0}^{2R} 2\rho L r E(r) \sin \phi dr

Now, clearly, by cosine rule,

cos ϕ = R 2 + r 2 R 2 2 R r = r 2 R \cos \phi = \dfrac{R^2+r^2-R^2}{2Rr} = \dfrac{r}{2R}

Hence, sin ϕ = 1 ( r 2 R ) 2 \sin \phi = \sqrt{1 - \bigg(\dfrac{r}{2R}\bigg)^2}

Thus ,

F = 0 2 R 2 ρ L r E ( r ) 1 ( r 2 R ) 2 d r F = \displaystyle \int_{0}^{2R} 2\rho L r E(r) \sqrt{1 - \bigg(\dfrac{r}{2R}\bigg)^2} \ dr

= 0 R 2 ρ L r ρ r 2 ϵ 0 1 ( r 2 R ) 2 d r + R 2 R 2 ρ r L ρ R 2 2 r ϵ 0 1 ( r 2 R ) 2 d r \displaystyle \int_{0}^{R}2\rho L r \dfrac{\rho r}{2 \epsilon_{0}} \sqrt{1 - \bigg(\dfrac{r}{2R}\bigg)^2} \ dr + \displaystyle \int_{R}^{2R} 2 \rho r L \dfrac{\rho R^2}{2 r \epsilon_{0} }\sqrt{1 - \bigg(\dfrac{r}{2R}\bigg)^2 } \ dr

Now, after the substitution r = 2 R sin t r = 2R \sin t ,

F = ρ 2 R 3 L ϵ 0 ( 0 π / 6 8 sin 2 t cos 2 t d t + π / 6 π / 2 2 cos 2 t d t ) F =\displaystyle \dfrac{\rho^2 R^3 L}{ \epsilon_{0}} \bigg( \int_{0}^{\pi/6} 8 \sin^2 t \cos^2 t dt + \int_{\pi/6}^{\pi/2} 2 \cos^2 t dt \bigg)

= ρ 2 R 3 L ϵ 0 ( π 2 3 3 8 ) = \boxed{\dfrac{\rho^2 R^3 L}{ \epsilon_{0}} \bigg(\dfrac{\pi}{2} - \dfrac{3 \sqrt{3}}{8} \bigg) }

Nice question Jatin!! Earlier I was marked wrong but I am really thrilled to see that my answer is actually correct! +1 for your solution as well ¨ \ddot\smile

Karthik Kannan - 6 years, 8 months ago

Same thing happened with me karthik Really amazing question

Akash Yadav - 3 years, 12 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...